2007
DOI: 10.1093/her/cym036
|View full text |Cite
|
Sign up to set email alerts
|

Do adolescents perceive police officers as credible instructors of substance abuse prevention programs?

Abstract: Although program recipients' attitudes toward instructors are crucial to program outcomes, they have not been adequately examined in the substance abuse prevention literature. This study uses survey data to explore attitudes toward instructors of prevention programming held by students from a national longitudinal evaluation of a school-based substance abuse prevention program delivered by Drug Abuse Resistance Education (D.A.R.E.) officers. Our analyses indicated that students who had police officers as instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…program, from which G.R.E.A.T. was loosely modeled, revealed that police officers who provided the instruction received better evaluations than nonpolice officer instructors (Hammond et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…program, from which G.R.E.A.T. was loosely modeled, revealed that police officers who provided the instruction received better evaluations than nonpolice officer instructors (Hammond et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These variables are related to several mentioned by Dusenbury and her colleagues (2005) as critical to prevention effectiveness, namely “teacher enthusiasm” and “student engagement.” Other characteristics that have been assessed include teachers’ “respectfulness,” “ability to understand students,” and “likeability” (Rohrbach, Dent, Skara, Sun, & Sussman, 2007), as well as teachers’ level of understanding of their students’ world (Hammond, Sloboda, Tonkin, Stephens, Teasdale, Grey, et al, 2008), “caring” and “support” (Wentzel, 1997), and “credibility” (Tonkin et al, in press). As mentioned earlier, there are clearly other dimensions that we have not tapped, and that remain to be suggested by theory or practical experience.…”
Section: Discussionmentioning
confidence: 99%
“…Engagement in unlawful activities, however, has been examined in a snowball sample of Canadian students and shown to be negatively related to the respondents' overall assessment of the police, measured by a single item (Chow, 2011). Another study illustrated that students who used drugs and students who were involved in greater deviance reported more negative views of police instructors of prevention program (Hammond et al, 2008). Only one study, relying on a sample of Chicago public school students, examined the effects of prosocial values on adolescents' respect for the police and willingness to assist the police .…”
Section: Social Bonds and Juvenile Perceptions Of The Policementioning
confidence: 99%